2015
DOI: 10.1002/anie.201507092
|View full text |Cite
|
Sign up to set email alerts
|

Delineating the Role of Helical Intermediates in Natively Unfolded Polypeptide Amyloid Assembly and Cytotoxicity

Abstract: Amyloid deposition is a hallmark of many diseases, such as the Alzheimer's disease. Numerous amyloidogenic proteins, including the islet amyloid polypeptide (IAPP) associated with type II diabetes, are natively unfolded and need to undergo conformational rearrangements allowing the formation of locally ordered structure(s) to initiate self-assembly. Recent studies have indicated that the formation of α-helical intermediates accelerates fibrillization, suggesting that these species are on-pathway to amyloid ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 37 publications
2
56
0
Order By: Relevance
“…There is still great debate on the above models and neither of them can interpret all experiment observations. For instance, a recent study showed that the hIAPP with D‐residues (D‐hIAPP) at positions 15 and 16 have equivalent kinetics of self‐assembly with the wild‐type hIAPP . Since the D‐residues could prevent the N‐terminal α‐helical folding, this study demonstrated the N‐terminal helix formation is irrelevant to the aggregation .…”
Section: Introductionmentioning
confidence: 78%
“…There is still great debate on the above models and neither of them can interpret all experiment observations. For instance, a recent study showed that the hIAPP with D‐residues (D‐hIAPP) at positions 15 and 16 have equivalent kinetics of self‐assembly with the wild‐type hIAPP . Since the D‐residues could prevent the N‐terminal α‐helical folding, this study demonstrated the N‐terminal helix formation is irrelevant to the aggregation .…”
Section: Introductionmentioning
confidence: 78%
“…4B). 40,41 The stabilisation of these membrane-bound α-helical states attenuates the formation of IAPP fibrils 41 and, as recent evidence suggests, decreases the cellular toxicity of IAPP. 41,42 This indicates therapeutic applications of IAPP helix stabilisers.…”
Section: Resultsmentioning
confidence: 99%
“…40,41 The stabilisation of these membrane-bound α-helical states attenuates the formation of IAPP fibrils 41 and, as recent evidence suggests, decreases the cellular toxicity of IAPP. 41,42 This indicates therapeutic applications of IAPP helix stabilisers. In our previous work, scaffolds functionalised with acidic, hydrophobic and acidic groups that overlay with positions i , i + 3/4 and i + 7 of an α-helix, respectively, were highly effective disruptors of membrane-catalysed IAPP fibrillation.…”
Section: Resultsmentioning
confidence: 99%
“…It does, however, diminish helicity 20 and cytotoxicity 21 . In contrast, a similarly motivated change in which residues 15 and 16 are replaced by D -amino acids diminishes helicity and yet increases cytotoxicity 22 . These contrasts suggest the presence and functional importance of molecular scale interactions.…”
mentioning
confidence: 99%